Spatial patterns of vineyard landscape evolution and their impacts on erosion susceptibility: RUSLE simulation applied in Mercurey (Burgundy, France) since the mid-20th century - Cossart, Étienne; Fressard, Mathieu; Chaize, Brian (ERDKUNDE, 2020)
Erosion susceptibility in vineyards is approximately one order of magnitude above the reference level calculated for all agricultural activities, and preventing soil erosion is thus one of the most important environmental issues in vineyards. Spatially explicit models are necessary to address the coevolution of erosion susceptibility and anthropogenic practices because of the heterogeneous spatial patterns of erosion within vineyards. In this paper, we apply the RUSLE model to assess erosion susceptibility through time in a Burgundy vineyard (Mercurey) at a catchment scale (15 km²). The model is first calibrated with data acquired in 2015-2018. Second, erosion susceptibility during former stages (1953 and 1984) is compared to current reference frame. Such theoretical comparison considers that both C (land cover) and LS (Length-Slope) factors evolved through time. We hypothesize that such factors reveal both the land use evolution (especially agricultural land uses) and the development of a soil erosion management strategy based on the collection of sediments using roads, hedges and ditches. The current reference frame of erosion susceptibility calculated at catchment scale is about 9,152 t.yr-1. In the early 1980s a peak in erosion susceptibility is concomitant with vineyard expansion during the second half of the 20th century. Erosion susceptibility in vine parcels in 1984 is estimated to be 32% higher than current period. In the mid-20th century the spatial patterns of agricultural land use (patchwork of grasslands and vines, vines on moderately-rugged hillslopes) led to moderate rates of erosion susceptibility. At this stage, past level of erosion susceptibility is estimated to be 40% lower than current reference frame.